Peran Bimbingan Penyuluhan Islam Dalam Meningkatkan Spritualitas Keagamaan Masyarakat Kampung Muallaf di Kecamatan Suka Maju Tanah Karo - Muhammad Habib Fedrian; Zikri Siregar; Hagiansyah Harahap; Alfi Syahri (Peneliti.net, 2022)
The purpose of this research is to find out and help converts to increase religious spirituality or faith and devotion to Allah Subhanahu Wata'ala for the Muallaf village community in Suka Maju Tanah Karo District. With the contents of the questions 1) What is the process of Islamic counseling in Suka Maju Tanah Karo District?, 2) What is the function of Islamic counseling guidance in Suka Maju Tanah Karo District?, 3) What are the results of Islamic counseling guidance in Suka Maju Tanah Karo District? The method used is descriptive qualitative with data collection techniques by observation, interviews and documentation, carried out systematically and factually by describing the state or status of phenomena. The results of Islamic counseling guidance in Suka Maju Tanah Karo District are the emergence of religious or spiritual spiritual aspects or faith and devotion to Allah Subhanahu wata'la such as the awareness to carry out prayers which are an obligation, leaving things that are prohibited, and supporting each other in carrying out religious activities. It can be concluded that Islamic counseling guidance in Suka Maju Tanah Karo District is very effective in helping to increase faith for the Muallaf Village Community in Suka Maju Tanah Karo District.